Explorando a utilidade da bioimpedância elétrica para avaliação da composição corporal em pacientes com câncer: novas perspectivas - Guedes, Francisco Felipe de Oliveira (2024)
Cancer is a disease with high incidence and mortality rates worldwide, causing significant impacts on public health. Among its various implications, it notably promotes changes in body composition (BC), which can worsen patient prognosis. Thus, monitoring BC is essential to optimize clinical care. To this end, it is indispensable to use assessment methods that are reliable, accessible, and practical. Among the available alternatives, bioelectrical impedance analysis (BIA) has gained prominence. In addition to being practical and cost-effective, BIA provides a detailed and functional view of BC, demonstrating potential to overcome some limitations of more complex and less accessible methods. In this context, the present study aims to explore the utility of BIA in evaluating BC in cancer patients, encompassing a comparative analysis between different BIA devices, as well as assessing the potential of phase angle (PhA) as a marker of muscle quality. To achieve this, two cross-sectional studies were conducted, including hospitalized adult and elderly cancer patients. Study 1 analyzed the correlation and agreement between BIA results obtained using two homologous single-frequency tetrapolar devices from different manufacturers (Sanny® and RJL Systems®). Device comparisons were performed considering both raw parameters [resistance (R) and reactance (Xc)] and derived estimates [fat-free mass (FFM) and PhA]. Study 2 evaluated the performance of PhA as a measure of muscle quality compared to indicators of skeletal muscle radiodensity (SMD), muscle quality index (MQI), and strength-to-muscle radiodensity index (SMRi), which were used as indicators of morphological, functional, and “morpho-functional” muscle quality, respectively. The 33rd percentile was used to classify low muscle quality based on PhA, SMD, MQI, and SMRi, using results from the study sample. Statistical correlation and agreement tests were applied, with P-values < 0.05 considered statistically significant. In Study 1, 116 patients were included, with a mean age of 60.8 ± 14.8 years, of whom 51.7% were women. Significant correlations were observed between the devices for all evaluated outcomes, with very strong correlations for R (rho = 0.971) and FFM (r = 0.979), and strong correlations for Xc (rho = 0.784) and PhA (rho = 0.768). However, the measurements obtained using the Sanny® device showed no agreement with those from the RJL Systems® device, with less satisfactory results for Xc and PhA, showing biases of -14.18% [35.67 – (-64.04)] and -13.33% [40.30 – (- 66.80)], respectively. While R and FFM demonstrated better performance, with biases of -0.91% [23.78 – (-25.60)] and -4.42% [26.14 – (-34.97)], respectively, the limits of agreement (95% CI) still demonstrated wide variation. In Study 2, 294 patients were included, with a median age of 62 years (59–69), of whom 53.7% were male. PhA showed a moderate correlation with SMD (rho = 0.48, P < 0.001) and a weak correlation with MQI and SMRi (rho = 0.22 and 0.26, respectively, P < 0.001). Moderate agreement was observed between low PhA and low SMD, while poor agreement was found when comparing low PhA with low MQI and SMRi values. Low PhA demonstrated moderate accuracy (AUC > 0.70) in classifying low SMD, and more modest accuracy in classifying low MQI and SMRi among men. In conclusion, BIA results are significantly influenced by the device manufacturer and the adequacy of the formulas applied to the equipment. Furthermore, PhA shows a modest capacity in classifying reduced muscle quality.